PERANCANGAN APLIKASI PENJUALAN MOBIL BEKAS DI CV SINGGALANG MOTOR PADANG BERBASIS WEB - Regina Aprilia; Muhammad Anwar (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
Progress of the programming field allows to build Web-based applications. This research was conducted to design used car sales by web-based applications in CV. Singgalang Motor Padang. This application is built for ease in conducting sales, purchasing and financial reporting. The sales and purchase transaction of car units is conducted online so that customers and sellers do not need to come the showroom. Application design uses the Unified Modelling Language (UML) model, diagram use case, activity diagram and sequence diagram. The application is built using the PHP language (Hypertext Preprocessor) with CSS (Cascading Style Sheets) as an additional language, while its editor uses SublimeText. Application uses JavaScript coding, the Framework CodeIgniter and MySQL as a database. The security techniques used in the application are encryption, session and delimiter permissions to each user. However this application has facilitated for customers in selling and buying cars, assisting transaction in browsing data collection, financial reporting, and sales reporting. Keywords: Information Systems, PHP, CodeIgniter, MySQL